PENGEMBANGAN MEDIA PERANGKAT PEMBELAJARAN BERBASIS PRAKTIKUM VIRTUAL UNTUK MENINGKATKAN KETRAMPILAN PROSES SAINS SISWA SMA - Aden Arif Gaffar; Muhamad Kurnia Sugandi (Jurnal Biotek, 2019)
Students difficulties in understanding topics during learning process has an impact on student learning outcomes. The virtual practicum allows students to explore and visualize the concept of learning in more detail and clearly than just a theoretical explanation especially in biology topics. The aim of this research is to develop learning media based on virtual practicum, and improve students' science process skills. The research is a R&D (Research and Development) using nontest in the form of a valid questionnaire. The results of virtual practicum media feasibility were 79% with good criteria, 76% content with good criteria, 78% linguistic with good criteria, and 95% practicality with very good criteria. An advance trial of the media was carried out in the academic year 2019/2020 in class X Senior High School 1 Sindangwangi, Majelengka districts. The results indicate that learning media tools based on virtual practicum has increase the science process skills of students.  The pretest value is 9.1% and increase to 88% in posttest. The value of t count 12.89> t table 2.24. Based on the results of the study it can be concluded that the media of virtual practicum-based learning tools is feasible to use and can improve the ability of students' science processes in the concept of invertebrates.